2014
DOI: 10.1016/j.ejor.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Issues Mapping: A problem structuring method for addressing science and technology conflicts

Abstract: a b s t r a c tThere are new opportunities for the application of problem structuring methods to address science and technology risk conflicts through stakeholder dialogue. Most previous approaches to addressing risk conflicts have been developed from a traditional risk communication perspective, which tends to construct engagement between stakeholders based on the assumption that scientists evaluate technologies using facts, and lay participants do so based on their values. 'Understanding the facts' is genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Pellizzoni, 2001;Borch and Rasmussen, 2005;Vergragt and Brown, 2008;Cronin et al, 2014). However, scholars (ibid) still emphasise that stakeholders', especially citizens', concerns, interests, and values are not fully integrated in the assessment and policy making of GM plants.…”
Section: Participatory Technology Assessment In Agriculturementioning
confidence: 95%
See 2 more Smart Citations
“…Pellizzoni, 2001;Borch and Rasmussen, 2005;Vergragt and Brown, 2008;Cronin et al, 2014). However, scholars (ibid) still emphasise that stakeholders', especially citizens', concerns, interests, and values are not fully integrated in the assessment and policy making of GM plants.…”
Section: Participatory Technology Assessment In Agriculturementioning
confidence: 95%
“…Overall, the authors found that the iterative questionnaires and workshops facilitated open dialogue amongst stakeholders supporting them in addressing and sharing different interests and perceptions. Cronin et al (2014) take a step further to include lay citizens in the GMO assessment and report how they carried out a participatory and iterative approach supported by models, engaging researchers and members of community interest groups (e.g. dealing with environmental, health, and sustainable agriculture issues).…”
Section: Participatory Technology Assessment In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of these methods has typically led to a well-defined set of principles and process steps. What has not changed, however, is the set of available methods (for some efforts see Gregory et al 2012;Cronin et al 2014). Although methods have been combined in a multimethodology fashion, such combinations have not led to a new method that integrates hard and soft aspects of modelling (Mingers 2000;Westcombe et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, we will draw on the knowledge-perspective of communication (Mengis & Eppler, 2008), and mainly concentrate on the work by Tsoukas (2009). His conceptualisation of knowledge creation is grounded in the notion of dialogue-type interactions, which are arguably a key characteristic of the facilitated modelling approach to group decision support (Cronin, Midgley, & Jackson, 2014;Franco, 2006).…”
mentioning
confidence: 99%